The Relationship Between Nurses’ Attitudes Toward Vital Signs Monitoring and Emotional Intelligence Levels - Nuray Turan; Türkinaz Aşti; Çiğdem Beki; Aysel Özsaban (Genel Tıp Dergisi, 2022)
Aim: The study aims to determine the relationship between nurses’ attitudes toward vital signs and emotional intelligence levels. Method: The descriptive and correlational study was conducted with 301 nurses. Data were collected using the Nurse Information Form, V-Scale and Emotional Intelligence Evaluation Scale. The data analyzed using descriptive and correlational statistics. Results: The V-Scale and Emotional Intelligence Evaluation Scale total scores average of the nurses were good level and no statistical relationship between them (p>0.05). However, remarkable relationships between the total and sub-dimension scores of the relevant scales were demonstrated. Communication, empathy, emotional awareness and managing skills are important competences for vital signs monitoring. Conclusion: Based on the findings obtained from the research, it can be concluded that nurses’ attitudes toward vital signs monitoring, and emotional intelligence could be affected different variables. In future, different types (experimental, qualitative etc.) of studies should be for explaining between nurses’ attitude to monitoring vital signs and emotional intelligence. Policy makers and managers should focus more on variables that affect nurses’ attitude to monitoring vital signs.